Simulation based education training: Knowledge and perception of the participants - Twi Twi , Jyotsana; Tamrakar, Alina; Thapa, Binu; Shrestha, Indira (Journal of Chitwan Medical College, 2025)
Introduction: Simulation-based education (SBE) uses simulated patients or aids to teach and coach healthcare professionals to gain competence in real-life clinical scenarios. The study aimed to assess the effectiveness of training program on acquisition of knowledge and perception regarding SBE and training. Method: With support from AMPATH Nepal, Nursing and Midwifery Program, Kathmandu University School of Medical Sciences organised a 5-day SBE training for 3 batches from Jul 2023 to Aug 2024. Ethical approval was obtained. A one-group pre- and post-test design using semi-structured questionnaires was used to evaluate knowledge and perceptions regarding SBE and training program. Data were analysed using SPSS 21, significance level set at p≤0.05. Result: Out of 60 participants, the mean difference in perception of SBE before and after training was significant (p<0.05) for eleven statements, including improved communication skills (p=0.045), managing rare cases (p<0.001), reduced stress compared to wards (p<0.001), superiority to bedside teaching (p=0.005), use as an adjunct not a replacement (p=0.016), importance of evidence (p=0.001) and interpersonal relationships (p=0.001), preparation of rating scales (p=0.007) and checklists (p<0.010), application in clinical subjects (p<0.001), and needs to ready materials/equipment beforehand (p=0.002). There was a significant difference between knowledge (p<0.001) and perception (p<0.001) regarding SBE before and after participation in the training. Conclusion: The SBE training led to significant improvements in participants' knowledge and perceptions. They also viewed the training as highly effective in enhancing their understanding of SBE.